Repertoire of the Practice of the Security Council: Supplement 1966-1968 - Nations Unies (United Nations, 1968)
This publication serves as a guide to the proceedings of the Security Council presenting an analytical indexed presentation of the practices and procedures since 1946. The current supplement covers the years 1966-1968. It deals with a period when the Council’s practice, in response to changes and new challenges on the international scene, considerably expanded in scope in the areas of conflict prevention, peacekeeping and electoral assistance. The Repertoire is designed to assist government officials, practitioners on international law, academics and all those interested in the work of the UN to gain a better understanding of the framework within which it operates. Texts of decisions on disputes and situations are accompanied by historical case summaries of the relevant chain of proceedings.